Fructose 1,6-bisphosphatase 1 is a potential biomarker affecting the malignant phenotype and aerobic glycolysis in glioblastoma - Weihong Lu; Guozheng Huang; Yihan Yu; Xia Zhai; Xiangfeng Zhou (PeerJ)
Background Fructose 1,6-bisphosphatase 1 (FBP1) has been considered as a potential prognostic biomarker in glioblastoma (GBM), and this study explored the underlying mechanism. Methods The expression and effect of FBP1 expression on the prognosis of GBM patients were examined applying bioinformatics analyses. After measuring the expression of FBP1 in normal glial cell line HEB and GBM cells, cell counting kit-8 (CCK-8), 5-ethynyl-2-deoxyuridine (EdU), colony formation, transwell, and wound healing assay were carried out to examine the effects of silencing FBP1 on the proliferation and invasion of GBM cells. Aerobic glycolysis was measured by calculating the extracellular acidification rate (ECAR) and oxygen consumption rate (OCR) of FBP1-silenced GBM cells. Furthermore, the protein levels of the mediators related to PI3K/AKT pathway and BCL2 protein family were detected via immunoblotting. Additionally, the effects of FBP1 silencing on the macrophage M2 polarization were assessed based on the fluorescence intensity of CD206 and the phosphorylation of STAT6 quantified by immunofluorescence and immunoblotting, respectively. Results High-expressed FBP1 was indicative of a worse prognosis of GBM. FBP1 knockdown in GBM cells suppressed the proliferation, invasion, migration, and aerobic glycolysis of GBM cells, lowered the phosphorylation levels of AKT and PI3K and the protein expression of BCL2 but promoted BAX protein expression. Moreover, FBP1 knockdown reduced CD206 fluorescence intensity and the phosphorylation of STAT6. Conclusion To conclude, FBP1 could be considered as a biomarker that affected the malignant phenotypes and aerobic glycolysis in GBM, contributing to the diagnosis and treatment of GBM.